Physical activity and exercise in peritoneal dialysis: International Society for Peritoneal Dialysis and the Global Renal Exercise Network practice recommendations. Issue 1 (January 2022) - Bennett, Paul N; Bohm, Clara; Harasemiw, Oksana; Brown, Leanne; Gabrys, Iwona; Jegatheesan, Dev; Johnson, David W; Lambert, Kelly; Lightfoot, Courtney J; MacRae, Jennifer; Meade, Anthony; Parker, Kristen; et al.
Life participation requiring physical activity and physical function is a key patient-reported outcome for people receiving peritoneal dialysis (PD). Clinician guidance is required from multidisciplinary sources regarding exercise and activity advice to address the specific needs of this group. From August 2020 through to June 2021, the Global Renal Exercise Network and the International Society for Peritoneal Dialysis reviewed the published literature and international clinical experience to develop a set of clinical practice points. A set of questions relevant to physical activity and exercise were developed from the perspective of a person receiving PD and were the basis for the practice point development. The GRADE framework was used to evaluate the quality of evidence and to guide clinical practice points. The review of the literature found sparse quality evidence, and thus the clinical practice points are generally based on the expert consensus of people receiving PD, PD exercise expert clinicians and experienced PD exercise researchers. Clinical practice points address timing of exercise and activity (post-catheter insertion, peritoneal space empty or full), the uptake of specific activities (work, sex, swimming, core exercise), potential adverse outcomes related to activity and exercise (exit site care, perspiration, cardiovascular compromise, fatigue, intra-abdominal pressure), the effect of exercise and activity on conditions of interest (mental health, obesity, frailty, low fitness) and exercise nutrition. Graphical Abstract This is a visual representation of the abstract.